1998
DOI: 10.1111/j.1349-7006.1998.tb03278.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Ginsenoside Rh2 on Tumor Growth in Nude Mice Bearing Human Ovarian Cancer Cells

Abstract: Cis-diamminedichloroplatinum(II) (CDDP) is considered as one of the most effective antitumor agents for ovarian carcinoma. CDDP-based chemotherapy has clearly improved the response rate in the treatment of ovarian carcinoma, but its clinical potential is often counteracted by intrinsic or acquired resistance and its impact on survival has been only marginal in most cases. Effective chemotherapy for ovarian carcinoma with such CDDP resistance is still not established. Thus, development of antitumor drugs which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
101
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(104 citation statements)
references
References 12 publications
3
101
0
Order By: Relevance
“…The systemic as well as oral multiple administrations of ginsenoside Rg3 inhibited lung metastasis produced by Bl6-BL6 melanoma and Colon 26-M3.l carcinoma cells in mice. This antimetastatic effect was thought to be associated with the inhibition of the invasion and adhesion by tumor cells as well as suppression of tumor-induced angiogenesis (72)(73)(74)(75)(76)(77). These results dealt mostly with induction of tumor cell differentiation, inhibition of tumor growths, prolongation of animal survival times or inhibition of metastasis.…”
Section: Identification Of Active Anticarcino-genic Components In Redmentioning
confidence: 95%
“…The systemic as well as oral multiple administrations of ginsenoside Rg3 inhibited lung metastasis produced by Bl6-BL6 melanoma and Colon 26-M3.l carcinoma cells in mice. This antimetastatic effect was thought to be associated with the inhibition of the invasion and adhesion by tumor cells as well as suppression of tumor-induced angiogenesis (72)(73)(74)(75)(76)(77). These results dealt mostly with induction of tumor cell differentiation, inhibition of tumor growths, prolongation of animal survival times or inhibition of metastasis.…”
Section: Identification Of Active Anticarcino-genic Components In Redmentioning
confidence: 95%
“…Unfortunately, very few data sets exist that allow tumors to grow large enough in order to get a proper estimate of the carrying capacity. We specifically sought out data sets that included data for large populations in order to properly compare the former two models with the latter three (Fujiwara et al, 1993;Takahashi et al, 1992;Murgo, 1985;Richmond et al, 1983;Kisfalvi et al, 2009;Reinmuth et al, 2002;Nakata et al, 1998;Caltagirone et al, 2000;Ricker et al, 2004).…”
Section: Ode Tumor Growth Modelsmentioning
confidence: 99%
“…The survival of tumor bearing mice was significantly increased (124 days in the control group, 198 days in the group treated with Rh-2 (120 M/day)), which suggested that the host-mediated immuno-potentiation of ginsenoside Rh-2 activated NK-cells. Nakata et al (29) reported that oral administration of ginsenoside Rh-2 (0.4-1.6 mg/kg/day) showed not only the anti-tumor activity in HRA-transplanted nude mice but also a significant increase of their survival (60 days in the control group, 85 days in the group treated with Rh-2 (0.4 S32mg/kg/day). It is noteworthy that the anti-tumor activity of ginsenoside Rh-2 against HRA cells is superior when orally administered than intra-peritoneally injected.…”
Section: Inhibition Of Tumor Angiogenesismentioning
confidence: 99%